Membedah Kasus Penistaan Agama oleh sang Murtad Kace - Mei Rahmawati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
In August 2021, Indonesia was shocked by the blasphemy incident by an Indonesian YouTuber. It is not surprising that this religious blasphemy exists because it often happens in Indonesia over and over again. Uniquely, the name of this religious blasphemer has the initials MK, which begins with the name of